Elizabeth - Kapur, Shekhar 1945-.; Owen, Alison; Fellner, Eric.; Bevan, Tim.; PolyGram Filmed Entertainment (Firm).; Channel Four Films (Firm).; Working Title Films (New York PolyGram Video, 1998)
Queen Elizabeth I must learn to weigh her counsel carefully and ignore her private yearnings if she is to keep her crown--and her head. A thriller of intrigue in the court of one of history's greatest monarchs.
VHS.
Golden Globe Award, Best Actress in a Drama.
Cate Blanchett, Geoffrey Rush, Christopher Eccleston, Joseph Fiennes, Richard Attenborough, John Gielgud.
Keywords: Elizabeth I -- Queen of England -- 1533-1603 -- Drama; Feature films; Great Britain -- Politics and government -- 1558-1603 -- Drama; Great Britain -- History -- Elizabeth, 1558-1603 -- Drama